Peningkatan Hasil Belajar Tematik Terpadu Peserta Didik Menggunakan Model Discovery Learning di Kelas V Sekolah Dasar - Reti Sumila; Yarisda Ningsih (Universitas Negeri Padang, 2023)
The low student learning outcomes in integrated subject learning is the driving force behind this research. In order to improve student learning outcomes, this study intends to describe how the discovery learning paradigm is applied in integrated theme learning in Elementary School. Classroom action research (CAR) was used in this study with qualitative and quantitative approaches. Planning, implementing, observing, and reflecting are the four processes covered in two cycles and three sessions. The results of organizing and observing practices using a discovery learning approach are related to research data. Check the documentation, observation, testing, and non-testing methods for collecting data. As many as 28 Class V students at SDN 12 Tanah Sirah Padang City acted as research participants, along with teachers who acted as observers and researchers who acted as practitioners. In the first cycle, the average result of the RPP research was 86.10%, and in the second cycle, the average research result was 94.44%. In cycle I, the average teacher evaluation score was 82.82%; in the cycle, II increased to 93.75%. The average score of students in all categories in the first cycle was 82.82%, but increased to 93.75% in the second cycle. Because students have a positive attitude towards KI-1 and KI-2, the attitude assessment in cycle I is good and very good in cycle II. Assessment of knowledge of the first cycle reached an average of 75.17 increased to an average of 88.92 in the second cycle; the skills assessment cycle I reached an average of 86.10 increased to an average of 92.94 in cycle II. It can be said that learning patterns were found that could improve the learning outcomes of fifth-grade students in learning based on thematic subjects.